2017
DOI: 10.30918/irjmms.53.17.029
|View full text |Cite
|
Sign up to set email alerts
|

Serum cholinesterase as liver function test in cirrhotic patients at Soba Teaching hospital, Khartoum, Sudan

Abstract: It is suggested that plasma cholinesterase level is affected by liver cirrhosis due to hepatocyte injury. The objective of this study was to determine cholinesterase values in association with albumin and prothrombin during both the compensated and decompensated stages in cirrhotic patients. A total of 150 consecutive episodes of liver cirrhotic patients, aged (68.9 ± 10 years) admitted to the hospital between June 2015 and December 2015 were studied. They were classified into subgroups according to severity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The result was statistically significant (p<.001). This was in agreement with the findings of Mohamed et al 6 , Thathiya et al 7 , and Ramachandran et al 8 . Mohamed et al found mean serum cholinesterase 2519.58 ± 3.2 U/L in cirrhotic patients and 5984.0 ± 1.9 U/L in controls.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…The result was statistically significant (p<.001). This was in agreement with the findings of Mohamed et al 6 , Thathiya et al 7 , and Ramachandran et al 8 . Mohamed et al found mean serum cholinesterase 2519.58 ± 3.2 U/L in cirrhotic patients and 5984.0 ± 1.9 U/L in controls.…”
Section: Resultssupporting
confidence: 94%
“…Mohamed et al found mean serum cholinesterase 2519.58 ± 3.2 U/L in cirrhotic patients and 5984.0 ± 1.9 U/L in controls. 6 In Ramachandran et al, median serum cholinesterase in cirrhotic patients was 1590 U/L (110-8143U/L) compared to controls 7886 U/L (2022-21673U/L), p < 0.001. 8 In the study of Thathiya et al, the level of serum cholinesterase was significantly lower in chronic liver disease patients (2314 ± 1413 U/L) when compared to controls (7883 ± 1012 U/L).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, a more precise and sensitive test for diagnosing liver disease is needed (4). Cholinesterases are a class of enzymes that catalyze the breakdown of the neurotransmitter acetylcholine, producing choline and acetic acid, a necessary process for cholinergic neurotransmission to be restored (5). Cholinesterases are classified into two types: acetylcholinesterase (AChE) and butyryl cholinesterase (BChE).…”
Section: Introductionmentioning
confidence: 99%